Changes in selected metabolic parameters in patients over 65 receiving hydrochlorothiazide plus amiloride, atenolol or placebo in the MRC elderly trial. Issue 1 (December 2016) - Damian, Damian; McNamee, Roseanne; Carr, Matthew
Abstract Background Treatment of hypertension reduces incidence of stroke, myocardial infarction and heart failure perhaps partly by controlling different metabolic parameters. There is limited information regarding the changes in potassium, sodium, weight, cholesterol and glucose levels in patients using anti-hypertensives. This study aimed to determine changes in potassium, sodium, glucose, cholesterol, weight, urea and urate levels in patients using anti-hypertensives. Furthermore, to describe these changes and differences between the atenolol, hydrochlorothiazide plus amiloride and placebo arms of the Medical Research Council (MRC) elderly randomised controlled trial. Methods Patients were randomly allocated to one of the three treatment arms. Measurements were taken at baseline, end of year one and end of year two in 4396 subjects. Linear Mixed Models (LMM) were used to determine the longitudinal profiles of sodium, potassium, weight, cholesterol, glucose, urea and urate. Estimates of changes within groups and difference between groups were obtained. Results Patients randomised to receive hydrochlorothiazide + amiloride experienced a significantly greater mean reduction in potassium, sodium and weight compared to placebo at end of year one - mean differences in change −0.18 mmol/L, (95 % CI: −0.21, −0.15); −1.45 mmol/L, (95 % CI: −1.62, −1.29) and −0.46 kgs (95 % CI: −0.73, −0.20) respectively, and greater increases in cholesterol, urea and urate - mean differences in change 0.16 mmol/L, (95 % CI: 0.10, 0.22); 0.77 mmol/L, (95 % CI: 0.68, 0.87) and 53.10 μmol/L, (95 % CI: 49.35, 56.85) respectively. Changes were in the same direction but smaller in the atenololarm except for potassium and weight (increases). No group differences in glucose were found. Conclusion Results were in line with expectation except for lack of change in glucose in the hydrochlorothiazide + amiloride arms.